Lanthanide ion (III) complexes of 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraaminophosphonate for dual biosensing of pH with chemical exchange saturation transfer (CEST) and biosensor imaging of redundant deviation in shifts (BIRDS). (6th May 2014) - Huang, Yuegao; Coman, Daniel; Ali, Meser M.; Hyder, Fahmeed
<x xml:space="preserve">Abstract</x> Relaxivity‐based magnetic resonance of phosphonated ligands chelated with gadolinium (Gd3+) shows promise for pH imaging. However instead of monitoring the paramagnetic effect of lanthanide complexes on the relaxivity of water protons, biosensor (or molecular) imaging with magnetic resonance is also possible by detecting either the nonexchangeable or the exchangeable protons on the lanthanide complexes themselves. The nonexchangeable protons (e.g. –CHx, where 3 ≥ x ≥ 1) are detected using a three‐dimensional chemical shift imaging method called biosensor imaging of redundant deviation in shifts (BIRDS), whereas the exchangeable protons (e.g. –OH or –NHy, where 2 ≥ y ≥ 1) are measured with chemical exchange saturation transfer (CEST) contrast. Here we tested the feasibility of BIRDS and CEST for pH imaging of 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraaminophosphonate (DOTA‐4AmP8−) chelated with thulium (Tm3+) and ytterbium (Yb3+). BIRDS and CEST experiments show that both complexes are responsive to pH and temperature changes. Higher pH and temperature sensitivities are obtained with BIRDS for either complex when using the chemical shift difference between two proton resonances vs using the chemical shift of a single proton resonance, thereby eliminating the need to use water resonance as reference. While CEST contrast for both agents is linearly dependent on pH within a relatively large range (i.e. 6.3–7.9), much stronger CEST contrast is obtained with YbDOTA‐4AmP5− than with TmDOTA‐4AmP5−. In addition, we demonstrate the prospect of using BIRDS to calibrate CEST as new platform for quantitative pH imaging. Copyright © 2014 John Wiley & Sons, Ltd.